Relationship of Urothelial Gene Expressions in Urine-Deprived Bladders of Renal Recipients With Posttransplant Urinary Infections - ATA, PINAR (ELSEVIER SCIENCE INC, 2015)
Objective. In this study, we analyzed gene expression levels of apoptotic (Fas, FasL, Bcl-2, Bax) and survival (CXCR1, CXCR2, IL-8) signal pathways of the urine-deprived bladder tissues and the relation of urinary tract infections with these pathways. Material and Methods. We included 37 patients admitted for renal transplantation between December 2009 and December 2012. Bladder mucosal samples were obtained at the time of transplantation and 6-8 weeks posttransplantation, at the time of ureteral catheter removal. RNA extraction and cDNA synthesis were done using guanidium-thiocyanate and colon filter methods. Expression analysis was studied with quantitative real-time polymerase chain reaction optimized with ROX dye and internal control beta-actin. Results. According to our findings Fas, FasL, Bcl-2, and Box expression was higher in urine-deprived bladder samples than those in the posttransplant samples (P < .05). Although Fas, FasL, Bcl-2, and Box expression levels increased in pretransplant samples, there was an increase in posttransplant bladder samples; however, this increase was not as marked as those of pretransplant samples. IL-8, CXCR1, and CXCR2 expression was decreased at the pretransplant samples and increased in posttransplant bladder samples. Conclusions. We have found an upregulated apoptotic process and decreased survival signals at the urine-deprived bladder tissue. After transplantation, bladder tissue survival parameters were increased, demonstrating the importance of urinary flow for bladder tissue.
Keywords: INTERSTITIAL CYSTITIS; CELL-SURVIVAL; INTERLEUKIN-8; DIFFERENTIATION; CHEMOKINES; UROEPITHELIUM; RECEPTORS; BIOLOGY; CANCER; CXCR1